Cervical screening result communication: a focus-group investigation of English women's experiences and needs. - Goldsmith, MR; Austoker, J; Marsh, G; Kehoe, S; Bankhead, C (2008)
OBJECTIVE: To explore English women's experiences of cervical screening result communication. DESIGN: Qualitative study consisting of seven focus groups conducted between May 2005 and April 2006. PARTICIPANTS: 33 women with a range of screening results (normal, inadequate, borderline and abnormal) who had recently been for cervical screening, and five women who had attended a colposcopy appointment for the first time following screening. SETTING: Three screening centres (Hampshire, Reading and Sheffield) and one colposcopy clinic (Oxford) in England. RESULTS: Unsatisfactory result communication (eg, delivery of out-of-date and conflicting information) on the part of both screening centres and primary care teams was highlighted. Variable levels of general practitioner involvement in screening result provision were experienced; result-giving strategies included personal as well as generic letters and telephone calls. Means for improving women's understanding of abnormal results were described including the use of diagrams to explain the progression of cell changes, the provision of updates regarding any changes in cell abnormalities between screening tests (ie, lesion progression or regression) and contact with a knowledgeable "intermediary" outside primary care. CONCLUSIONS: The timely provision of appropriate information is an important aspect of any screening programme. Our findings suggest that there is scope for improvement in both the delivery and content of cervical screening result notifications. Regular review of patient result-giving strategies on the part of screening centres and general practices could help ensure that screening programme standards for written information are met. Enhanced communication between primary care teams and screening centres could facilitate the provision of consistent and clear result messages thereby improving women's cervical screening experiences.